ANALISIS PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA STAP PENDIDIK DI STIKES. PUTRA ABADI LANGKAT - Rita Ernawati (Jurkessutra : Jurnal Kesehatan Surya Nusantara, 2020)
Maximal and qualified  achievement of intructors’ performance in Implementing the Three Principles of Education: education, research, and public service need capacity the process of education and training which are in accordance with their qualification. The objective of this research was to analyze the influence of education and training on the intructors’ performance at STIKes Putra Abadi Langkat. The research used associative method  with 52 respondents as the samples. The data where gathered by using questionnaires of intructors’ performance with the indicator of the Three Principles of Educuation (education, research, and public service), completed by interviews and analyzed by using Pearson Product Moment test. The result of the research showed that 84.6% of the respondents had good education, 82.7% of the respondents had good education and training, 84.6% of the respondents had moderate performance based on the aspects of the Three Principles of Educaciton (education, research, and public serveice), 65.38% of the respondents had good performance based on the category of education and learning, 90.38% of the respondents had lack of performance based on the category of research, and 80.76% of the respondents had lack of performance based on the category of public service. The result of correlation analysis on education and training showed that there was significant correlation between training and performance. The result of multiple liear regression analysis showed that education had the influence on instructors’ performance (p=0.578) and training had the influence on intructors’ performance (p=0.622). it is recommended that the management of the institution evaluate instructors’ performance in carrying out the Three Principles of Education and make the supporting policies in order to achieve the indicator of optimal and equal performance for all aspects of the Three Principles of Education